Literature review on the applicability of Tanaka and Johnston’s predictive analysis of the mesio-distal size of unerupted permanent canines and premolars in Africa - Dzaringa, Gboro Teddy; Mayunga, M. G.; Nyengele, K. A.; Nzudjom, F. Adelin; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Lindondo, E. P. (Orapuh Journal, 2025)
The Tanaka-Johnston analysis is a widely adopted orthodontic method for predicting the mesio-distal widths of unerupted permanent canines and premolars based on the dimensions of mandibular incisors. Despite its popularity, the method was developed using data from Caucasian populations, raising concerns about its accuracy and relevance for individuals from other ethnic backgrounds, including African populations. This literature review aims to evaluate the validity and applicability of the Tanaka-Johnston analysis for African populations. The goal is to determine whether this method provides reliable estimates for mixed dentition analysis in these populations and to identify any necessary modifications or alternative predictive equations. A systematic literature search was conducted using PubMed, Google Scholar, and Scopus. Keywords used included: Tanaka-Johnston analysis, mixed dentition, canine premolar width, and Africa. Inclusion criteria comprised studies that directly assessed the applicability or accuracy of the Tanaka-Johnston method in African populations. Studies focusing on non-African populations or not evaluating the Tanaka-Johnston analysis were excluded. The review included several studies from various African countries. Findings revealed variability in the accuracy of Tanaka-Johnston predictions across different African ethnic groups. Some studies reported overestimation or underestimation of tooth sizes, indicating that the original regression equations may not be universally applicable. Several authors proposed population-specific adjustments or alternative equations to improve predictive accuracy for African children. Although the Tanaka-Johnston analysis remains a valuable tool, its unmodified use in African populations demonstrates limited accuracy. Ethnic variability in tooth size necessitates the development or adaptation of population-specific predictive models to ensure accurate orthodontic assessment and treatment planning. Future research should focus on developing and validating such models tailored to diverse African demographics.